Investigation on the Factors Influencing Employee Turnover in Hospitality Industry in Kabale Municipality: A Case Study of Cephas Inn. - Vallence, Ayebazibwe (Kabale University, 2024)
Employee training was one-factor influencing employee turnover in the hospitality industry. Several studies continue to indicate hospitality as the most significant factors that influence tourist satisfaction this positively increases the level of tourism development, but the extent to which these cases are associated with hospitality industry trends is not known. This study aimed to fill this research gap. A cross-sectional study in which a mixed method of inquiry was used to collect data using a questionnaire. The questionnaire had both open and closed-ended questions to capture both quantitative and qualitative responses. A sample of study participants was drawn from the elements affecting tourists’ level of satisfaction. A total sample of 33 participants was selected. Result: Of the 33 participants that were interviewed, the highest number 48.5% belonged to the age group of 21-30 year males with 57.6% whereas the least number of respondents were females with 42.4% considering the age of respondents, Conclusion: Employee turnover has affected the performance of the hospitality industry, The study found that employee turnover and development was 72.4% being the most various factors that have increased the performance of the hospitality industry this finding positively increases employee turnover and indicates that it most employee training that is prevalently being used in the hospitality industry in Kabale municipality. The study proposed the following recommendations; Increase awareness among hotels and accommodations about new technologies, Develop and implement intervention programs to address new employee training, Train employees on new technologies and the benefits of promoting and developing hotel and accommodation facilities, and Conduct further research to gain a better understanding of the complex relationship between technology use, hotel and accommodation facilities, and tourism in the context of kabale municipality.